ANTARCTIC CLIMATE AT THE EOCENE/OLIGOCENE BOUNDARY - CLIMATE MODEL SENSITIVITY TO HIGH LATITUDE VEGETATION TYPE AND COMPARISONS WITH THE PALAEOBOTANICAL RECORD - Thorn V.C.; DeConto R. (My University, 2006)
Simulated climate for the Antarctic continent using the GENESIS (Version 2.1) Global Climate Model with 34 Ma boundary conditions is shown to be highly sensitive to polar vegetation type. Six experiments were run using different levels of atmospheric CO2, orbital configurations, ice sheet geometries and vegetation types to assess model sensitivity to Antarctica being covered with either a needle leaf evergreen forest or tundra. Simulations using 2× pre-industrial levels of CO2 (combined mean annual temperature (MAT) - 19°C) are about 7°C cooler than minimum estimates from the Antarctic Cenozoic plant record (MAT - 12 to 15°C). However, simulations using 3× CO2 (MAT - 7°C) are in good agreement with our empirical estimates of mean annual temperature. With ice sheets and orbits set up to represent early Oligocene interglacial conditions, the tundra climate is significantly cooler than the evergreen forest climate, with local, austral summer averages up to 6°C cooler in non-glaciated areas and continental averages ~2.5°C cooler. In the model this is mainly due to higher albedo and decreases in net radiation and sensible and latent heat flux, especially during spring and summer. Feedbacks between coastal and continental cooling, marginal sea surface temperatures and sea ice also appear to be significant. A review of the late Palaeocene to earliest Miocene plant fossil record in the Antarctic Peninsula and Ross Sea regions shows that the vegetation was in transition ~34 Ma, from a relatively diverse, mainly evergreen forest to a tundra vegetation. The modelled sensitivity of continental temperatures to a change from forest to tundra suggests vegetation-climate feedbacks during the Eocene-Oligocene transition played a significant role in the initial rapid glaciation of the continent. © 2005 Elsevier B.V. All rights reserved.
Keywords: ANTARCTICA; CENOZOIC; GLOBAL CLIMATE MODELS; GREENHOUSE-ICEHOUSE TRANSITION; PALAEOBOTANY; PALAEOCLIMATE; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен